The Attachment Of Client Photo During The Signing Of The Authentic Minutes Deed - Hengky -; Mohamad Fajri Mekka Putra (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze the urgency of attaching the photo of the person at the time of signing the deed in the minutes of the deed and to examine more deeply the position of the photo as evidence in the trial. The form of this research is juridical-normative which relies on written legal sources with a research typology that is explanatory and in the form of prescriptive. The type of data used in the form of secondary data sourced from primary, secondary and tertiary legal materials with qualitative data analysis methods. Attaching a photo of the person at the time of signing the deed in the minutes of the deed is expected to further guarantee the Notary in carrying out his obligations in the deed inauguration process, so that he does not only adhere to the presence of fingerprints which also have the potential to be taken at different times, because essentially the role of affixing fingerprints on the sheet separate evidence is as additional evidence if the appearer denies his signature and guarantees that the appearer is actually dealing with the notary at the time of signing the deed, but does not guarantee that the signing is done at the same time